COMPARATIVE ANALYSIS OF THE US IMPORTATION SEASONALITY OF WOODEN MOLDINGS MADE OUT OF BRAZILIAN AND CHILEAN CONIFERS - Valerius, Jaqueline; Da Silva, João Carlos Garzel Leodoro; Timofiecsyk Júnior, Romano; Steiner Neto, Pedro José (Floresta, 2022)
Conifer wood moldings are classified as high value-added wood products and are used for several purposes in civil construction. Brazil is the world’s leading exporter of this product and the United States are its main destination market. It is very important to analyze the behavior of such importations and exportations to set strategies to obtain or increase the competitive advantage and improve the commercialization of these products. The objective of this study was to analyze the US importation seasonality of conifer wood moldings from Brazil and Chile, the main competitor of the Brazilian product in the US market. To write this paper, monthly data of the quantity of US importations of Brazilian and Chilean moldings from the period of 2011 to 2017 were collected from the database of the United States Department of Agriculture/Foreign Agricultural Service. The methodology proposed by Hoffman (2006) was employed to calculate the seasonal and seasonality indexes. The results indicated that the US importation of conifer wood moldings, both from Brazil and Chile, have a seasonal behavior, with great variation of the seasonal index.